Reimagining colonial Qingdao: between historical fact and commodification - Philipp Demgenski (Built Heritage)
Abstract Colonial heritage in China remains a contested and multifaceted subject, representing both a reminder of national humiliation by foreign powers and a resource for tourism and urban branding. Under the current leadership, the revival of cultural heritage has become increasingly aligned with narratives emphasising civilisational unity and nationalism, complicating the representation and utilisation of colonial remnants. This complexity is evident in the case of Qingdao’s old city centre. With its German colonial-era cobblestone streets and Art Nouveau architecture, it evokes a European rather than a Chinese urban landscape. For various urban actors, including the local government, the tourism sector, and local intellectuals, Qingdao’s colonial heritage represents a meaningful resource, albeit with divergent political and cultural rationales. This paper explores how these groups leverage and even celebrate Qingdao’s colonial heritage without contradicting the state-sanctioned narrative of ‘national humiliation’. They achieve this feat by framing the colonial past either as a neutral, fact-based history or as a marketable commodity, thus rendering it depoliticised and ahistorical. Ultimately, this paper sheds light on the broader status of postcolonial discourse in contemporary China, revealing how colonial legacies are navigated within the constraints of nationalistic narratives.